Arab Feminist philosophy: The Question of Essence and Development (مجلة جامعة سرت للعلوم الانسانية, 2025)
This study aims to identify one of the feminist intellectual currents or movements that emerged in the Arab world with cultural and social contents. It took a philosophical pattern as an attempt to reconcile social reality with openness to the outside world, taking among its objectives the most important issues, namely the pursuit of women’s liberation, the break with her religion and the culture of her society, and her equality with man in political, economic, and social rights. This is centered on the question of essence through the woman’s position in her society on the one hand, and the question and affirmation of her identity, her liberation, and her equality with man on the other hand.
Keywords: Feminist; Essence; Development; Contemporary Arab Discourse